MEDIA AS THE ALCHEMIST OF SOCIETAL PERCEPTION: NAVIGATING THE COMPLEX MAZE OF INFLUENCE, RESPONSIBILITY, AND NARRATIVE ALCHEMY - Ronald Alfredo; Karnawi Kamar; Adi Mursalin; Iyad Abdallah Al- Shreifeen; Aceng Haetami (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
In the exploration titled "Media as the Alchemist of Societal Perception: Navigating the Complex Maze of Influence, Responsibility, and Narrative Alchemy," the study delved into the intricate dynamics of media's role as a transformative force. The research in the past tense unfolded against the backdrop of an evolving media landscape, where mass media transcended its conventional role to become a modern alchemist. The investigation aimed to unravel the multifaceted dimensions of media's influence, scrutinizing its ethical responsibilities and engaging with the alchemy of narrative construction. As media, akin to an alchemist, wielded the tools of linguistic and visual elements, the study explored how it actively shaped societal consciousness. The journey through this exploration revealed that media, in its contemporary incarnation, went beyond being a mere disseminator of information. It emerged as an active participant in crafting narratives that influenced collective perceptions, navigating a labyrinth where the boundaries between reality and perception blurred. The study scrutinized the ethical considerations accompanying media's transformative role, delving into the delicate balance between informative storytelling and potential narrative manipulation. Simultaneously, it focused on the alchemy of narrative construction, unraveling how media transformed raw information into narratives resonating with the collective consciousness. This past-tense reflection encapsulates the nuanced exploration undertaken, shedding light on the transformative power of media in shaping societal perceptions and leaving the groundwork for a deeper understanding of the intricate dynamics that define its role as a modern alchemist